DAMPAK PRODUK, HARGA DAN SELERA KONSUMEN TERHADAP PENJUALAN SEPEDA MOTOR PADA PT. ASTRA HONDA MOTOR DI KABUPATEN MERAUKE - Abdul Kadir (Jurnal MEDIAN Arsitektur dan Planologi, 2020)
Impact of Products, Prices and Consumer Tastes on Sales at PT. Astra Honda Motor in Merauke Regency The population used is as many as 94 respondents. Multiple linear regression analysis shows the following results: Y = 1.671 + 0.188X1 + 0.269X2 + 0.157X3 The results of the analysis show that the t-value of the product variable (X1) is 2.217, a significant level of 0.001, while the t-table value with alpha 0.05 where N = 94, df = 4, the value is 1.661. Where the value of tcount> ttable is 2.217 > 1.661 or the level of the sig <alpha value is 0.029 <0.05, thus H0 is rejected and Ha is accepted, namely the product (X1) has a positive and significant effect on expenditure (Y). The results of the analysis of the t value of the variable price (X2) are 2.944, a significant level of 0.004, while the t-table value with alpha 0.05 where N = 94, df = 4, the value is 1.661. Where the value of tcount> ttable is 2.944> 1.661 or the level of the sig <alpha value is 0.004 <0.05, thus H0 is rejected and Ha is accepted, namely price (X2) has a positive and significant effect on expenditure (Y). The results of the t-value analysis of the consumer taste variable (X3) were 1.775, a significant level of 0.003, while the t-table value with alpha 0.05 where N = 94, df = 4, obtained a value of 1.661. Where the value of tcount> ttable is 1.775> 1.661 or the level of the sig <alpha value is 0.003 <0.05, thus H0 is rejected and Ha is accepted, namely consumer taste (X3) has a positive and significant effect on expenditure (Y). The results of simultaneous analysis show that Fcount,> Ftable is 17.601> 2.70 or the sig <alpha value is 0.000 <0.05, thus Ho is rejected and Ha is accepted, that is, simultaneously the product, price and consumer tastes have a positive and significant effect on expenditure in PT. Astra Honda Motor.